Ultrasound-Mediated Cancer Therapeutics Delivery using Micelles and Liposomes: A Review - Mukhopadhyay, Debasmita (2021)
Nanoparticles have proven promising as cancer theranostic tools. Nanoparticles are selective in nature, have reduced toxicity, and controllable drug release patterns making them ideal carriers for anticancer drugs. Numerous nanocarriers have been designed to combat malignancies, including liposomes, micelles, dendrimers, and, more recently, metal organic frameworks. The temporal and spatial release of therapeutic agents from these nanostructures can be controlled using internal and external triggers, including pH, enzymes, redox, temperature, magnetic and electromagnetic waves, and ultrasound. Ultrasound is an attractive modality because it is non-invasive, can be focused on the diseased site, and has a synergistic effect with anticancer drugs. This review will focus on the use of ultrasound-mediated liposomes and polymeric micelles in cancer therapy.